The effect of amantadine on an ion channel protein from Chikungunya virus. - Debajit Dey; Shumaila Iqbal Siddiqui; Prabhudutta Mamidi; Sukanya Ghosh; Chandra Shekhar Kumar; Soma Chattopadhyay; Subhendu Ghosh; Manidipa Banerjee (Public Library of Science (PLoS), 2019)
Viroporins like influenza A virus M2, hepatitis C virus p7, HIV-1 Vpu and picornavirus 2B associate with host membranes, and create hydrophilic corridors, which are critical for viral entry, replication and egress. The 6K proteins from alphaviruses are conjectured to be viroporins, essential during egress of progeny viruses from host membranes, although the analogue in Chikungunya Virus (CHIKV) remains relatively uncharacterized. Using a combination of electrophysiology, confocal and electron microscopy, and molecular dynamics simulations we show for the first time that CHIKV 6K is an ion channel forming protein that primarily associates with endoplasmic reticulum (ER) membranes. The ion channel activity of 6K can be inhibited by amantadine, an antiviral developed against the M2 protein of Influenza A virus; and CHIKV infection of cultured cells can be effectively inhibited in presence of this drug. Our study provides crucial mechanistic insights into the functionality of 6K during CHIKV-host interaction and suggests that 6K is a potential therapeutic drug target, with amantadine and its derivatives being strong candidates for further development.